2020
DOI: 10.1152/ajplung.00235.2019
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase-α amplifies transforming growth factor-β-dependent profibrotic signaling in lung fibroblasts

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a progressive fibrosing lung disease for which treatment remains suboptimal. Fibrogenic cytokines, including transforming growth factor-β, are central to its pathogenesis. Protein Tyrosine Phosphatase-alpha (PTPα) has emerged as a key regulator of fibrogenic signaling in fibroblasts. We have reported that mice globally deficient in PTPα (Ptpra-/-) were protected from experimental pulmonary fibrosis, in part via alterations in TGF-β signaling. The goal of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 105 publications
1
12
0
Order By: Relevance
“…In this study, we investigated the expression of CB 1 R in lung fibroblasts isolated from BLM-challenged mice and found that CB 1 R mRNA levels were significantly increased in the isolated lung fibroblasts from mice with BLM-induced pulmonary fibrosis compared with control mice ( Figure 3A ), which is in accordance with the increased CB 1 R mRNA levels in lung tissues of pulmonary fibrosis mice ( Figure 1A ). TGF-β1 is one of the most potent and well-studied profibrotic inducers of pulmonary fibrosis that triggers and greatly enhances the fibrogenic activity of lung fibroblasts ( Fernandez and Eickelberg, 2012 ; Martinez et al, 2017 ; Aschner et al, 2020 ; Lee et al, 2020 ). We isolated primary mouse lung fibroblasts to examine the expression of CB 1 R and ECM proteins induced by TGF-β1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we investigated the expression of CB 1 R in lung fibroblasts isolated from BLM-challenged mice and found that CB 1 R mRNA levels were significantly increased in the isolated lung fibroblasts from mice with BLM-induced pulmonary fibrosis compared with control mice ( Figure 3A ), which is in accordance with the increased CB 1 R mRNA levels in lung tissues of pulmonary fibrosis mice ( Figure 1A ). TGF-β1 is one of the most potent and well-studied profibrotic inducers of pulmonary fibrosis that triggers and greatly enhances the fibrogenic activity of lung fibroblasts ( Fernandez and Eickelberg, 2012 ; Martinez et al, 2017 ; Aschner et al, 2020 ; Lee et al, 2020 ). We isolated primary mouse lung fibroblasts to examine the expression of CB 1 R and ECM proteins induced by TGF-β1.…”
Section: Resultsmentioning
confidence: 99%
“…In the pathogenesis of pulmonary fibrosis, lung fibroblasts are activated under the stimulation of profibrotic cytokines and exhibit a series of cell behavior changes, such as proliferation, migration, and ECM production, which is associated with severity of the disease in patients with pulmonary fibrosis and mouse models of pulmonary fibrosis ( Xia et al, 2014 ; DePianto et al, 2015 ; Kasam et al, 2020 ). TGF-β family proteins, especially TGF-β1, released by injured lung epitheliums, immune cells, and fibrocytes during pulmonary fibrosis, are considered the principal profibrotic cytokines that drives fibrotic responses ( Fernandez and Eickelberg, 2012 ; Martinez et al, 2017 ; Aschner et al, 2020 ; Lee et al, 2020 ). TGF-β signals are generally transduced through TGF-β type I and type II receptors (TβRI and TβRII) and Smads, and ancillary proteins as well ( Aschner et al, 2020 ; Lee et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, DEC1 overexpression induced EMT in vitro . TGF-β1, a crucial mediator in tissue fibrosis, is a significant factor in promoting EMT and the development of PF ( Akhurst and Hata, 2012 ; Aschner et al, 2020 ). We also found that Dec1 KO alleviated BLM-induced upregulated expression of TGF-β1 in BALF in mice.…”
Section: Discussionmentioning
confidence: 99%
“…There has been renewed interest in molecules such as members of the cellular communication network (CCN) ( 12 ) and the insulin-like growth factor (IGF) ( 3 , 22 ) family of proteins and their functions in the setting of lung fibrosis. Moonlighting functions for enzymes such as sialidases ( 11 ) and phosphatases ( 1 , 18 , 21 ) have been identified. Research into mechanisms mediating oxidative stress and its role in lung fibrosis has continued ( 6 ).…”
mentioning
confidence: 99%